Analysis of the Effect of Apparatus Competence, Organizational Commitment, Community Participation, Utilization of Information Technology and Transparency on Accountability of Village Fund Management - Solikhah, Mar’atus; Hossain, Md. Jakir (Publikasi Indonesia, 2024)
The purpose of this study is to determine and analyze the effect of apparatus competency analysis, organizational commitment, community participation, use of information technology and transparency, on village fund management decisions (Village Case Study in Gempol District, Gempol Regency). The testing in this study was carried out with multiple linear regression analysis, t hypothesis test and F test. With multiple linear regression analysis in this study, b1 = 0.273 results showed a positive influence between the variables of Apparatus Competence (X1) on Village Fund Management Accountability, b2 = 0.586 showed a positive influence between the variables of Organizational Commitment (X2) on Village Fund Management Accountability, b3 = 0.351 shows a positive influence between the variables Community Participation (X3) on Accountability of Village Fund Management, b4 = 0.233 shows a positive influence between the variables of Information Technology Utilization (X4) on Accountability of Village Fund Management, b5 = 0.421 shows a positive influence between the variables of Transparency Utilization (X5) on Accountability of Village Fund Management. As for partial hypothesis testing, the t test was used, obtained the calculated t value for the Apparatus Competency variable (X1) of 2.687, tcalculate for the Organizational Commitment variable (X2) of 2.411, tcalculate for the Community Participation variable (X3) of 2.620, tcalculate for the Information Technology Utilization variable (X4) of 2.181, tcalculate for the Transparency variable (X5) of 2.552, with ttable criteria of 1.998 used in the test Ini.